PEMBANGUNAN EKONOMI WILAYAH KABUPATEN CIAMIS BERBASIS KOMODITAS PETERNAKAN - Agus Yuniawan Isyanto; Sudrajat Sudrajat; Dedi Herdiansah Sujaya (Universitas Galuh Ciamis, 2018)
The study was conducted with the aim to analyze the economic development of Ciamis District based on livestock sector. The data used are secondary data in the form of population of 7 livestock commodities from 26 subdistricts in Ciamis Distict. The data were analyzed quantitative descriptive by using Location Quotient (LQ) analysis. The results showed that some subdistricts in Ciamis District were the base areas for beef cattle, sheep, goats, domestic poultry, laying chicken, broiler and duck.Keywords: Economic development, LQ, Commodities, Livestock